Exploring the Influence of Programming Courses on University Students’ Computational Thinking Skills - Darwas, Rahmadini; Sepriana, Rina; Rahimullaily, Rahimullaily; Jalinus, Nizwardi; Ambiyar, Ambiyar; Giatman, Giatman (Jurnal Teknologi Informasi dan Pendidikan, 2025)
This study aims to explore the relationship between students' perceptions of programming courses and computational thinking (CT) skills in Information Systems Study Program students at Metamedia University. The sample consisted of 37 semester students in the 2024/2025 academic year. The research method used was quantitative with a correlational approach, and data analysis was carried out using the JASP application. The results of the Spearman's rho correlation test showed a value of 0.103 with a p-value of 0.590. This value indicates a very weak and insignificant relationship between perceptions of programming courses and CT skills, as measured by the Mid-Semester Exam scores. This finding indicates that although students have positive perceptions of programming courses, these perceptions are not necessarily directly proportional to their CT skills. This result contradicts initial expectations that assume a strong relationship between positive perceptions and increased CT skills. The implications of this study indicate the need to develop a learning approach that explicitly integrates CT elements in the learning process, assignments, and assessments in programming courses in higher education